2020
DOI: 10.4067/s0718-22442020000100141
|View full text |Cite
|
Sign up to set email alerts
|

Entre el macizo del deseado y la margen norte de la cuenca del Río Santa Cruz (Patagonia, Argentina): Análisis geoquímico de artefactos de obsidiana y modelos de circulación humana

Abstract: La alta frecuencia de obsidiana en algunos sectores de este espacio y la mención de pobladores locales acerca de la existencia de fuentes desconocidas hasta el momento llevaron a la necesidad de explorar esta hipótesis. Se realizaron análisis geoquímicos mediante fluorescencia de rayos X a una muestra de 20 artefactos de obsidiana. Los resultados indican una composición geoquímica similar a las fuentes secundarias de Pampa del Asador, su cono aluvial y 17 de Marzo o sectores intermedios entre ellas, lo que deb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
32

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 13 publications
0
2
0
32
Order By: Relevance
“…It is also noteworthy the joint presence of obsidian from different sources, distant from each other, which would demonstrate the circulation of groups around several different spaces and/or the existence of extensive exchange circuits. Finally, it is important to mention the absence of obsidian from Pampa del Asador, whose distribution in Patagonia is very wide (Ambrústolo et al, 2012; Banegas et al, 2021; Belardi et al, 2006; Castro Esnal et al, 2012; Cruz et al, 2011; Cueto et al, 2018; Fernández et al, 2015; Franco et al, 2020; Gómez Otero et al, 2017; Reyes et al, 2015; Stern, 2017; among others). This absence had already been detected in the case of coastal sites and has been corroborated now in the inland ones, reaffirming our previous proposal that the obsidian from Pampa del Asador did not reach regions located further north of the coast of Chubut province (Alberti, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also noteworthy the joint presence of obsidian from different sources, distant from each other, which would demonstrate the circulation of groups around several different spaces and/or the existence of extensive exchange circuits. Finally, it is important to mention the absence of obsidian from Pampa del Asador, whose distribution in Patagonia is very wide (Ambrústolo et al, 2012; Banegas et al, 2021; Belardi et al, 2006; Castro Esnal et al, 2012; Cruz et al, 2011; Cueto et al, 2018; Fernández et al, 2015; Franco et al, 2020; Gómez Otero et al, 2017; Reyes et al, 2015; Stern, 2017; among others). This absence had already been detected in the case of coastal sites and has been corroborated now in the inland ones, reaffirming our previous proposal that the obsidian from Pampa del Asador did not reach regions located further north of the coast of Chubut province (Alberti, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In Patagonia in general, obsidian is a widely distributed raw material that appears in different contexts. According to Stern (2017) and Franco et al (2023), south of the 37th parallel, 10 different sources of obsidian have been identified from which this raw material was dispersed by humans at distances greater than 300 km from their place of origin. In this area of southernmost Argentina, other obsidian sources with narrower distributions have also been identified, and, in addition, a few different types of obsidian, whose sources are still unknown, are recorded in some archaeological sites (Stern, 2017).…”
Section: Obsidians In the Río Negro Province Coast And Surrounding Areasmentioning
confidence: 99%
“…Previamente al Holoceno tardío, la información disponible nos lleva a suponer que una interacción suprarregional y rangos de acción muy amplios pudieron estar involucrados en la distribución de los instrumentos laminares. Al respecto, Langlais y Morello (2009) propusieron que los instrumentos laminares del abrigo Cerro Castillo 1 mantendrían una vinculación con el complejo Casapedrense (Menghin 1952), que, entre otras características, se compone de una tecnología de hojas empleada principalmente para la manufactura de cuchillos y raspadores entre aproximadamente 7.300 aP y 3.300 aP (Aschero 1987;Gradin 1980) -aunque también existe una producción asistemática de láminas al sur de la cuenca del Río Santa Cruz aproximadamente entre los 6.200 aP y 4.800 aP (Franco y Vetrisano 2014;Franco et al 2016). Por su parte, Martin y Borrero (2017) sostienen que las primeras ocupaciones en el Cerro Benítez-Lago Sofía fueron producto de la explotación logística de pobladores tempranos asentados en el CVPA, a unos 150 km del Cerro Benítez-Lago Sofía.…”
Section: Discussionunclassified
“…Estos han sido empleados en general para entender la movilidad e interacción humana, así como los cambios en la utilización de los recursos líticos a través del tiempo. Se han combinado análisis geoquímicos, estudios de base geológica macro y microscópicos y, más recientemente, la modelación con SIG para entender la movilidad y circulación humana en distintas latitudes, habiéndose incorporado a través del tiempo perspectivas que enfatizan la importancia de aspectos biogeográficos (Barberena et al 2019;Castro 2015, Castro et al 2014, 2020Franco et al 2015Franco et al , 2018Franco et al , 2020Cortegoso et al 2016Cortegoso et al , 2017Gilio et al 2022;Pallo y Borrazzo, 2016;Salgán y Pompei 2017).…”
Section: La Circulación Humanaunclassified